2014
DOI: 10.1016/j.cytogfr.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The TWEAK-Fn14 pathway: A potent regulator of skeletal muscle biology in health and disease

Abstract: TNF-like weak inducer of apoptosis (TWEAK), a TNF superfamily ligand, and its bona fide receptor, the TNF receptor superfamily member fibroblast growth factor-inducible protein 14 (Fn14), represents a pivotal axis for shaping both physiological and pathological tissue responses to acute or chronic injury and disease. In recent years significant advances have been made in delineating the prominent role of this axis in regulating skeletal muscle mass and metabolism. Also emerging from the broad study of tissue i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 76 publications
(171 reference statements)
3
64
0
2
Order By: Relevance
“…The inflammatory cytokine TWEAK and its receptor Fn14 negatively regulate skeletal muscle growth and function (104). However, recent in vivo studies using pharmacological and genetic modulation of TWEAK and Fn14 have also demonstrated a role for this pathway in the development of pathological cardiac hypertrophy, fibrosis, LV remodeling and dysfunction, and heart failure (31,51,81,85).…”
Section: Current Treatment Of Cardiac Atrophy In Cancer Cachexiamentioning
confidence: 99%
“…The inflammatory cytokine TWEAK and its receptor Fn14 negatively regulate skeletal muscle growth and function (104). However, recent in vivo studies using pharmacological and genetic modulation of TWEAK and Fn14 have also demonstrated a role for this pathway in the development of pathological cardiac hypertrophy, fibrosis, LV remodeling and dysfunction, and heart failure (31,51,81,85).…”
Section: Current Treatment Of Cardiac Atrophy In Cancer Cachexiamentioning
confidence: 99%
“…TWEAK is a member of the TNF superfamily of cytokines and an important stimulus for the activation of NF-B signaling in skeletal muscle (39,40). TWEAK R, the smallest member of the TNF superfamily, has been identified as the unique TWEAK R (28,31,35).…”
Section: E757 Heightened Tweak-tweak R-nf-b Signaling In Sci Musclementioning
confidence: 99%
“…TWEAK R contains a TRAF binding site (9), which leads to downstream signaling and NF-B transcriptional regulation upon stimulation by TWEAK. TWEAK R is expressed at low levels in healthy tissues, and its expression significantly increases in response to injury, aging, disuse (40), and acute resistance exercise (33). Short-term TWEAK-TWEAK R activation promotes tissue repair and regeneration following an acute injury; however, during chronic injury or disease conditions, sustained TWEAK-TWEAK R activation may drive these responses toward a pathological remodeling in the muscle in which healthy tissue is replaced by fibrotic tissue (15,39,40).…”
Section: E757 Heightened Tweak-tweak R-nf-b Signaling In Sci Musclementioning
confidence: 99%
See 1 more Smart Citation
“…In similar fashion, as the environmental demands change due to prolonged inactivity or chronic disease states, the skeletal muscle responds by initiating signaling cascades that lead to muscle atrophy or wasting in a context-dependent manner 10 . Skeletal muscle mass is maintained through a delicate balance between the rate of protein synthesis and degradation 2,11 .…”
Section: Signaling Mechanisms Regulating Skeletal Muscle Massmentioning
confidence: 99%